The Education System in Swaziland : Training and Skills Development for Shared Growth and Competitiveness - Marope, Mmantsetsa (World Bank, 2012)
In September 2007, the Government of the Kingdom of Swaziland (GoS) approved a broad national development reform agenda in the form of a poverty reduction strategy and action plan (PRSAP). The plan is intended to update and operationalize the National Development Strategy (NDS) of 1999, as well as to begin to actualize Vision 2022; which was also launched in 1999.The ultimate outcome of these instruments is 'improved quality of life for all Swazis.' Their key goal is 'growth acceleration with equity or accelerated and shared growth.' A critical intermediate goal expressed in the PRSAP is a 30 percent reduction in poverty by 2015, and ultimate poverty eradication by 2022. It is estimated that reaching these targets will require a five percent average annual Gross Domestic Product (GDP) growth over a sustained period of time. This report presents an analysis of the adequacy of Swaziland's education, training and skills development sector (ETSDS) to effectively contribute toward addressing the outlined challenges and toward achieving national development goals presented in the PRSAP. Key sector weaknesses are identified and recommendations for their redress are made.